Analisis Produksi Ozon dalam Reaktor Dielectric Barrier Discharge Plasma (DBDP) Terkait Panjang Reaktor dan Laju Alir Udara Serta Pemanfaatannya untuk Menjaga Kualitas Asam Amino Ikan - Teke, Sosiawati; Nur, Muhammad; Winarni, Tri A (BERKALA FISIKA, 2014)
Characterization of the reactor Dielectric Barrier Discharge Plasma (DBDP) has performed as a generator of ozone (O3) and as sources of input air. Ozone was measured on a variation of the voltage (4-8 kV) with the speed of air flow of 0,5, 1, 1, 3, 4, 5, 6, 8 and 10 L/min. Plasma reactor was used as ozone generators with spiral-cylinder configuration. Spiral electrodes were made of copper wire diameter of 1,2 mm, coil length 50 mm and diameter cylindrical electrodes while 10,3 mm of cooper sheets with thickness 0,25 mm. Dielectric material used is pyrex with diameter 2 cm and 1,1 mm for its thickness. The AC voltage was used as plasma generators with frequency of 16 kHz. This Research used plasma reactor with three length variations that are 5, 10 and 15 cm . Results showed voltage, the length reactor and air flow rate input affects the ozone concentration. Ozone concentration increased while increasing voltage, the length of reactor and the flow rate used is small. Amino acids quality in short bodied mackerel (Rastrelliger sp.) fed ozone for 12 days of storage showed that ozone could maintain the quality of short bodied mackerel amino acids . Key Words: Spiral-cylinder Electrodes, Ozone Concentrations